Halal industry, digital economy, and creative economy: challenges and opportunities for MSMEs in Indonesia - Hermawan Adinugraha, Hendri; Khoirul Fikri, Muhammad; Andrean, Rizky (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2024)
This research aims to analyze the challenges and opportunities faced by MSMEs in Indonesia in simultaneously utilizing the halal industry, digital economy, and creative economy. The method used is qualitative, with case studies involving in-depth interviews, observation, and analysis of related documents. The focus of this research is to identify the main obstacles, such as halal certification bureaucracy, low digital literacy, and limited global market access, as well as opportunities that arise from the integration of these three sectors. The research results show that digitalization facilitates MSMEs in increasing market access and operational efficiency through sharia e-commerce and fintech platforms. Meanwhile, the creative economy encourages innovation in halal products that add value and are relevant to modern consumer trends. However, MSMEs still need help in technology adoption and innovative financing. This research underscores the need for cross-sector collaboration and government policy support to create an inclusive and sustainable business ecosystem. With an adaptive strategy, MSMEs in Indonesia can take advantage of the synergy between the halal industry, digital economy, and creative economy to compete in the global market and contribute to national economic growth